2012
DOI: 10.1007/s11259-012-9549-3
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the body temperature of cows and calves using video recordings from an infrared thermography camera

Abstract: The aim of this study was to assess the variability of temperatures measured by a video-based infrared camera (IRC) in comparison to rectal and vaginal temperatures. The body surface temperatures of cows and calves were measured contactless at different body regions using videos from the IRC. Altogether, 22 cows and 9 calves were examined. The differences of the measured IRC temperatures among the body regions, i.e. eye (mean: 37.0 °C), back of the ear (35.6 °C), shoulder (34.9 °C) and vulva (37.2 °C), were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(88 citation statements)
references
References 16 publications
1
80
1
6
Order By: Relevance
“…This was confirmed by principal factor analysis in the afternoon, because the values had higher weights for thermographic measurements of the udder (lat-udder and post-udder) and rectal temperature, which is in agreement with Hovinen et al (2008). Infrared thermography scans the surface temperature of the animal (Hoffmann et al, 2013), which varies with blood flow to the tissues and the amount of heat lost to the environment (Gil et al, 2013). Therefore, the optimal region found to identify the animal under heat stress in our study was the udder, due to extensive blood flow.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…This was confirmed by principal factor analysis in the afternoon, because the values had higher weights for thermographic measurements of the udder (lat-udder and post-udder) and rectal temperature, which is in agreement with Hovinen et al (2008). Infrared thermography scans the surface temperature of the animal (Hoffmann et al, 2013), which varies with blood flow to the tissues and the amount of heat lost to the environment (Gil et al, 2013). Therefore, the optimal region found to identify the animal under heat stress in our study was the udder, due to extensive blood flow.…”
Section: Discussionmentioning
confidence: 73%
“…Recent studies have shown that infrared thermography can be a useful tool for assessing stress and animal welfare (Stewart et al, 2005) and there are speculations about its application in the area of animal health and production (Berry et al, 2003). The measurement of body temperature is commonly used to check the health of the animal, but the method used (rectal temperature measurement) may cause stress and therefore lead to misleading results (Hoffmann et al, 2013). Infrared thermography is an alternative, as it is a modern, safe, and non-invasive visualization technique of the thermal profile Knížková et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…As médias das temperaturas da vulva variaram entre 33ºC no mês de maio, até 38,3ºC no mês de abril, semelhante à faixa de temperatura com média de 35,0 ± 2,4ºC [27]; Hoffmann et al [11] obtendo média de 37,2°C e de 36,90 ± 0,50°C [24]. A despeito das diferenças das origens genéticas, da geografia e do clima, verifica-se padrão similar para as faixas de temperatura da vulva em vacas de leite.…”
Section: Discussionunclassified
“…It is the key to obtain comparable and repeatable data within a period of time. Researchers (Hoffmann et al, 2012;Schaefer et al, 2012) have adapted automatic devices for temperature recording using a software comparing pictures in order to obtain reliable data.…”
Section: Discussion About the Different Methods To Measure Remote Temmentioning
confidence: 99%
“…Potential uses of the IR method for the early detection of diseases in cattle are studied by many authors (Schaefer et al, 2004;Hoffmann et al, 2012 ;Poikalainen et al, 2012), the latter proposing a fully automated system of measurement installed close to the livestock waterers. Montano et al (2009) showed that the IR technique, especially on the extremities of the body, is relevant to the study of feed efficiency of steers.…”
Section: Temperature Measurement With Non Invasive -No Contact Sensorsmentioning
confidence: 99%